(untitled) (Journal of the College of Basic Education, 2022)
From the terms of the concept of violation: The concept of exception. - The concept of inventory. Each one of them has his own style in the Arabic language, and they may meet for a purpose. My only statement is: (Exclusion). The grammatical significance of (restriction), which is rhetorically termed (reducing) a statement Limiting the adjective to the one who is described, as in the words of the Most High:  It is You we worship and You we seek help (1)  Or shorten Described on the adjective as the Almighty said:  You are only a warner of those who fear it (2) .